(3GdeHGOF GdYGeI aj GdbGfhf GdJLGQj (B/s - (3eMeOjf, LdGd haGAs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s)
(3jJfGhd gPG GdcJGH GdeHGOiA GdYGeI aj GdbGfhf GdJLGQj aj GdehVhYGJ fXQjI GdCYeGd GdJLGQjI hGdJGLQ hGdTQcGJ GdJLGQjI eGgjI GdbGfhf GdJLGQj , ehVhYGJ aj GdbGfhf GdJLGQj ,aj JWhjQ GdbGfhf GdJLGQj (B-(3fXQjI GdCYeGd GdJLGQjI ,aj eVehf GdYed GdJLGQj,GdCYeGd GdJLGQjI GdehVhYjI ,GdCYeGd GdJLGQjI GdJHYjI GdeNJdWI,CgejI GdJejjR Hjf GdCYeGd (B-(3fXQjI GdJGLQ,aj GcJSGH UaI GdJGLQ ,GdJRGeGJ GdJLGQ (B-(3GdTQcGJ ,GdCMcGe GdYGeI ,YbO Gdfbd ,GdJhSW GdJLGQj(B-(3YedjGJ GdHfhc ,GdMSGH GdJLGQj ,YbO aJM GdGYJeGO GdHSjW hGdeSJfOj ,Gdfbd GdHMQjs
Keywords: (3GdbGfhfs; (3GdbGfhf GdJLGQjs